2020
DOI: 10.1080/09658211.2020.1745848
|View full text |Cite
|
Sign up to set email alerts
|

What eye movements reveal about strategy encoding of words in younger and older adults

Abstract: The main goal of this study was to explore the organizational strategies used by younger and older adults when encoding words, using eye-tracking. Participants had to learn a set of organizable words and then a set of non-organizable words, each presented on a single display. Participants were then asked to recall the words of each set in the order in which they came to their mind. Hence, the participants' encoding strategies revealed by eye-tracking could be directly related to their subsequent memory perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(33 citation statements)
references
References 74 publications
7
26
0
Order By: Relevance
“…In this condition, only younger adults benefited from using this strategy as evidenced by the positive association between the ARC score and recall. These results are in line with a wide literature showing that older adults have difficulties to spontaneously implement semantic organisation during recall and that when implemented, the strategies are less efficient for memory than for younger adults (Denney, 1974;Taconnat et al, 2009, Taconnat et al, 2020 , but also other mnemonic strategies in diverse memory tasks (e.g., Burger et al, 2017) . Although we did not test for any cognitive control abilities, there is growing evidence that one reason why older individual fail to implement semantic organisation in a memory task where the words as organisable but not organised is due to lower working memory capacities (e.g., Cherry et al, 2021;Kuhlmann & Touron, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In this condition, only younger adults benefited from using this strategy as evidenced by the positive association between the ARC score and recall. These results are in line with a wide literature showing that older adults have difficulties to spontaneously implement semantic organisation during recall and that when implemented, the strategies are less efficient for memory than for younger adults (Denney, 1974;Taconnat et al, 2009, Taconnat et al, 2020 , but also other mnemonic strategies in diverse memory tasks (e.g., Burger et al, 2017) . Although we did not test for any cognitive control abilities, there is growing evidence that one reason why older individual fail to implement semantic organisation in a memory task where the words as organisable but not organised is due to lower working memory capacities (e.g., Cherry et al, 2021;Kuhlmann & Touron, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…These results have since been replicated, revealing that those who spontaneously use this semantic organisation retrieve more words (Denney, 1974;Puff, 1979) . Interestingly, although older adults always show lower recall performance than younger adults, some studies have reported that older adults do use semantic organisation spontaneously with a gain in performance, whereas other research has reported deficits regarding the use of this strategy (e.g., Howard & Kahana, 1999;Taconnat et al, 2009, Taconnat et al, 2020West & Thorn, 2001) . Although the use of semantic organisation may be spared in older adults (Golomb et al, 2008) , a recent eye-tracking study by Taconnat et al (2020) showed that older adults at least try to semantically organise the words during encoding, but fail to use this strategy at recall as compared to younger adults.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations